Inside the Hall of Silence (a biostratigraphically correct poem ) - Beyers, Joanna (UnderCurrents: Journal of Critical Environmental Studies, 1996)
1. South of Sidney, BC Time is the sculpted element. In this moment, opposite the rock that is James Island [...]